If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
y+6 = (2/3)*(x-4) // - (2/3)*(x-4)
y-((2/3)*(x-4))+6 = 0
(-2/3)*(x-4)+y+6 = 0
y-2/3*(x-4)+6 = 0
y-2/3*(x-4)+6 = 0
y-2/3*x+8/3+6 = 0
y-2/3*x+26/3 = 0
y-2/3*x+26/3 = 0
y-2/3*x+26/3 = 0 // - y+26/3
-2/3*x = -(y+26/3) // : -2/3
x = (-(y+26/3))/(-2/3)
x = 3/2*(y+26/3)
x = 3/2*(y+26/3)
| 93=2x+3(4x-11) | | 3q*16=2q+12 | | ab^2+4b^2=0 | | -2x+5y=30 | | 3-x=5+3x | | 5x/2+12=99 | | 20=2(7x-4) | | 4x-10=6x+28 | | 3x+2=5x-9 | | -8=b+6 | | 3x+8=36 | | 32=4-9y | | -4x+8x=5(x+2)-(x+10) | | 4x+5=7x-7 | | 50=5y | | 19.3=4.1+7.6b | | x^(2/5)^5/6 | | 3+4x=2x-7 | | 12=-6+d | | 20-4x=5x+2 | | 64^(-1/3) | | -3(c+4)=6 | | 2y-42+-y=6 | | a+7=-8 | | 2(x-7)+3y=-5 | | 0=-4.9t^2+25t-45 | | 0.6(s+4)=3 | | 4x^3+8x^2-x+2=0 | | 5x^(4/9) | | 12x^2-72x+77=0 | | 11x-4=x+32 | | w--3=18 |